Evaluation on fatigue strength of AISI 4340 steel aluminum coated by electroplating and IVD processes - Voorwald, Herman Jacobus Cornelis [UNESP]; Peres, Mauro Pedro [UNESP]; Pitanga Costa, Midori Yoshikawa [UNESP]; Hilario Cioffi, Maria Odila [UNESP] (Springer, 2010)
In spite of toxicity, hydrogen embrittlement susceptibility, and environmental issues, cadmium electroplating is usually applied on high strength AISI 4340 aeronautical steel due to its efficient protection against electrochemical corrosion. Ion vapor deposition (IVD) process with pure aluminum also offers good protection against corrosion with the advantages of decreasing hydrogen embrittlement susceptibility and improving the fatigue strength of metallic components. In this research, the effects of aluminum electroplating and IVD aluminum coating on the rotating bending fatigue strength of AISI 4340 steel were evaluated in comparison with cadmium electroplated specimens. Experimental fatigue results showed that both aluminum electroplating and IVD aluminum coatings are possible alternatives to cadmium electroplating.